Psychological well-being and resilience in youth at risk: a sistematic review - Díaz-Esterri, Jorge; De-Juanas, Ángel; Goig-Martínez, Rosa M. (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In the next few years, young people will be a population sector that will find itself in a particular situation of social risk. Thus, there is a need to identify what research relates the factors that influence positive psychological functioning and generate protective capital against social exclusion. This article presents a systematic review aimed at investigating the relationship between the development of resilience processes and psychological well-being in young people at social risk. This study leads to a series of conclusions that invite us to establish new lines of research on this topic.